Effect of the Power Balance® hologram on balance, flexibility, strength and speed-coordination among university students - Rafael Merino Marban, Daniel Mayorga Vega, Emilio Fernández Rodríguez, Francisco José Santana Pérez, Oscar Romero Ramos (FEADEF, 2011)
Based on the body's energy field, the inventors of Power Balance® have created a hologram that theoretically runs through frequencies that are in our natural environment. Its creators say that people may experience improve balance, strength, flexibility, endurance, concentration, coordination and recovery time, among others. The purpose of this research is to evaluate the effect of Power Balance® hologram on balance, flexibility, strength and speed-coordination in university students. A sample of 105 young volunteers' physical education students (age 20.91 ± 3.36 years, mass 69.69 ± 11.35 kg, height 171.70 ± 8.07 cm) was used. A between-group experimental design with double-blind control group was used to evaluate the possible effects of the Power Balance ® on the dynamic balance, flexibility, abdominal strength, endurance and speed-coordination measured with the Dynamic Balance Test, Sit and Reach, Sit-ups in 30 seconds and Race 10 x 5 m, respectively. A t of Student for independent and dependent samples was used to assess the potential effects between-group and intra-group, respectively. Power Balance®'s hologram produces no significant effects on the balance, flexibility, strength and speed-coordination among university students